Hasil Belajar Siswa Kelas 3 SDN Gayungan II Materi Operasi Hitung Perkalian menggunakan Jarimatika - Putri Nabiella Fitri Rahmadhani; Tri Nidia Kusumawardani; Priyono Tri Febrianto; Khusnul Laili Mansuroh (Lembaga Yasin AlSys, 2025)
The limited research on the effectiveness of the Jarimatika method in primary school mathematics instruction serves as the background for this study, particularly regarding its potential to enhance conceptual understanding of multiplication among lower-grade students. The objective of this research is to analyze the effectiveness of the Jarimatika method in improving student learning outcomes on multiplication operations. A qualitative approach with a descriptive design was employed, involving third-grade students at SDN Gayungan II/423 Surabaya, selected through purposive sampling. Data were collected through interviews with the classroom teacher, observations of student learning activities, and documentation, and analyzed descriptively. The findings indicate that the Jarimatika method has a significant impact on improving student learning outcomes, despite the continued dominance of lecture-based instruction. The study concludes that Jarimatika is an effective concrete-visual approach for facilitating students’ understanding of basic mathematical concepts, particularly multiplication. The implications include strengthening the literature on concrete-based mathematics instruction and offering practical recommendations for broader adoption of the Jarimatika method by teachers. This research also opens avenues for further exploration of Jarimatika's application to other mathematical topics and for testing its effectiveness using quantitative methods.